Bridging the Compliance Gap: How Trust in Zakat Institutions Influences Payment Behavior Among South Sulawesi Civil Servants - Sulkarnain; Multazam Mansyur Addury; Amira Husnul Khatimah; Jaswarni (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2026)
Introduction: This study aims to analyze the impact of the moderating variable of trust on the relationships between religiosity, zakat regulation, social pressure, and zakat compliance among State Civil Apparatus (ASN) in South Sulawesi. Research Methods: Employing a quantitative approach, data were collected from 150 ASN respondents residing in South Sulawesi. The hypotheses were tested using Moderated Regression Analysis (MRA). Results: The findings indicate that trust and religiosity have a direct, positive, and significant effect on zakat compliance. Conversely, zakat regulation and social pressure do not exert a significant direct influence. Crucially, trust acts as a significant moderator: it strengthens the positive effect of religiosity and, more importantly, activates a significant positive effect of zakat regulation on compliance. The moderating effect of trust on the relationship between social pressure and compliance was not found to be significant. Conclusion: The study concludes that institutional trust is a critical catalyst for zakat compliance, capable of enhancing spiritual motives and unlocking the potential of regulatory frameworks.